2010
DOI: 10.1094/pdis-03-10-0183
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Purification, and Biological Activity of a Phytotoxin Produced by Stemphylium solani

Abstract: Stemphylium solani, the causal agent of leaf blight of garlic (Allium sativum), produced phytotoxic metabolites in culture. A non-host-specific phytotoxin from culture filtrate of S. solani isolate DY-5, named SS-toxin, was extracted by ethyl acetate, isolated by bioassay-guided thin layer chromatography on silica gel, and purified by preparative liquid chromatography. SS-toxin produced necrotic lesions on detached garlic leaves, similar to that caused by S. solani. When wounded leaves were each treated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The introduction of a wheat oxalate oxidase gene in tomato reduced disease symptoms in plants infected by Botrytis cinerea or Sclerotinia sclerotiorum , two necrotrophic fungi producing oxalic acid, a toxin that is considered to be an important factor determining pathogenicity. In the same line of thought, a correlation between partial resistance and toxin resistance has been found in two other plant-necrotrophic fungal pathogen interactions: Allium sativum - Stemphylium solani [22] and Hevea brasiliensis - Corynespora cassiicola (V. Pujade-Renaud, personnal communication). To our knowledge, the discovery of partial resistance mechanisms based on QRLs and linked to a pathogen-produced toxin has never been published.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…The introduction of a wheat oxalate oxidase gene in tomato reduced disease symptoms in plants infected by Botrytis cinerea or Sclerotinia sclerotiorum , two necrotrophic fungi producing oxalic acid, a toxin that is considered to be an important factor determining pathogenicity. In the same line of thought, a correlation between partial resistance and toxin resistance has been found in two other plant-necrotrophic fungal pathogen interactions: Allium sativum - Stemphylium solani [22] and Hevea brasiliensis - Corynespora cassiicola (V. Pujade-Renaud, personnal communication). To our knowledge, the discovery of partial resistance mechanisms based on QRLs and linked to a pathogen-produced toxin has never been published.…”
Section: Introductionmentioning
confidence: 66%
“…Conversely, fungal toxins from Rhizoctonia solani and Sarocladium oryzae were shown to inhibit defense-related compounds in rice cell suspensions [51] . A link between plant pathogen partial resistance and toxin resistance has been suggested in the Allium sativum – Stemphylium solani pathosystem [22] but, to our knowledge, the present study is the first example where in vitro cell viability and embryogenic ability were used as an indicator of fungal toxin plant resistance. In our study, we adapted cell viability measurement methods based on measuring esterase activity using FDA as a substrate to carrot cell suspension cultures.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Given defined host-pathogen interactions, specific toxins were employed to promote symptoms [20,21,22]. Therefore, it is of great significance to elucidate the toxin arsenal and its bioactivities, as well as the relationship between toxins and fungal pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated that the enzymes and toxins produced by fungal pathogens during infection contributed largely to disease development [ 9 , 11 ]. Given defined host-pathogen interactions, specific toxins were employed to promote symptoms [ 20 , 21 , 22 ]. Therefore, it is of great significance to elucidate the toxin arsenal and its bioactivities, as well as the relationship between toxins and fungal pathogenicity.…”
Section: Discussionmentioning
confidence: 99%